"Kejahatan Seksual Pedofilia Dalam Perspektif Hukum Pidana dan Islam" - Eko Setiawan (Jurnal Hukum Islam, 2016)
Sexual crimes of pedophilia will have a negative impact for children.Not only undermine the future of the physical, but also mental andpsychological damage the child, such as major depressive disordermay be brought later into adulthood. Moreover, most people withpedophilia caused because he had been the victim of sexual abuse similarin childhood. The criminal acts of pedophilia is very detrimental to thevictims and the wider community. Therefore, the victims need care andprotection of the law. The law in Indonesia that ensnare the practice ofpedophilia was not serious. So that the penalty for pedophiles is notcommensurate with what has been done and the risk of future damageto the victims. Besides the protection of the public for the victims ofpedophiles are also very less.